Autocrine regulation of root hair size by the RALF‐FERONIA‐RSL4 signaling pathway. Issue 1 (29th March 2020) - Zhu, Sirui; Martínez Pacheco, Javier; Estevez, José M.; Yu, Feng
Summary: Root hair (RH) size has vital physiological implications, since it influences the surface area of the root and thus the ability of the plant to absorb water and nutrients from the soil. Arabidopsis ROOT HAIR DEFECTIVE 6‐LIKE 4 (RSL4), a bHLH transcription factor, controls the expression of hundreds of RH genes, and RSL4 expression itself can trigger ectopic RH growth. Recent studies reveal an autocrine mechanism governing plant RH cell growth in which the extracellular peptide RAPID ALKALINIZATION FACTOR 1 (RALF1) and receptor FERONIA (FER) act as a central hub between the cell surface and downstream signaling events. RALF1‐FER promotes the phosphorylation of eIF4E1. Then, phosphorylated eIF4E1 further regulates the synthesis of RH proteins, including RSL4, to promote RH growth. High levels of RSL4 exert a negative feedback on RALF1 expression via directly binding to the RALF1 gene promoter, slowing RH growth and determining final RH cell size.